ANALISIS STRATEGI PENINGKATAN PENDAPATAN USAHA MIKRO KECIL MENENGAH PADA MASA PANDEMI COVID-19 DALAM PERSPEKTIF HUKUM ISLAM - Ahmad Maulana; Irvan Iswandi; Alfi Satria (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Micro, Small and Medium Enterprises (MSMEs) play a role in the development and growth of the country's economy. MSMEs have different characteristics from large businesses, especially MSMEs, which are labor-intensive businesses located in rural locations, are more oriented towards local raw materials, and provide the main goods and services for the basic needs of people who have low incomes. This study aims to understand the MSME income-increasing strategy and understand the Perspective of Islamic Law on income-increasing strategies. The researcher uses a qualitative approach and this type of research is field research. The researcher uses primary and secondary data with three data collection techniques, namely observation, documentation, and interviews. The object of research in this study are the actors who own (MSMEs) in Gantar Village. The results of the study show that, 1) SMEs make many strategic changes, they adopt a survival strategy, dare to add goods/products and services, use mobile and online selling systems. MSMEs do not get business funding assistance from the government because the program is not on target. 2) Based on the perspective of Islamic law, good and humble service, having the courage to defend their business, being honest and trustworthy in buying and selling activities, and being consistent in business is a strategy to increase income. The majority of MSMEs in Gantar Village are self-owned and buying and selling transactions have an element of debt and credit but do not lead to usury. Then buying and selling is carried out with an Islamic principle contract by selling halal products. The implementation of the strategy to increase MSME income in Gantar Village has not fully implemented the Islamic law strategy, because there are still several MSME actors who get their capital from mobile bank loans (emok banks).